Ollier Disease: A Case Series and Literature Review - Markevičiūtė, Vėtra; Markevičiūtė, Medeinė Šilenė; Stravinskas, Mindaugas (Acta medica Lituanica, 2021)
Background. Ollier disease is the most common nonhereditary type of enchondromatosis. Enchondromas are common, usually benign intraosseous cartilaginous tumors that form near the growth plate cartilage predominantly unilaterally in the metaphyses and diaphyses of tubular bones. They usually affect the long bones of the hand, the humerus, and the tibia, followed by flat bones, such as the pelvis. The estimated prevalence of Ollier disease is 1 in 100,000 and while it is linked with somatic heterozygous mutations in IDH1 or IDH2 genes, exact etiology is unknown. The risk of malignant transformation towards chondrosarcoma is up to 30–35% and it is clinically suspected when pain and a rapid increase in the size of the lesions is seen.Case presentations. We report two clinical cases of patients diagnosed with Ollier disease. In both cases transformation to chondrosarcoma was observed.Conclusions. Ollier disease is a rare disorder, defined by the presence of multiple enchondromas and an asymmetric distribution of the cartilage lesions that can be extremely variable in terms of size, location, age, gender. Constant monitoring of patients is important due to the high risk of malignancy. Because the disease is very rare and the manifestations vary widely, each patient’s case must be evaluated, and the treatment strategy adopted individually.
Keywords: Ollier disease; enchondroma; chondrosarcoma; echondromatosis